Time-Based Design Paradigms - Barbara, Anna; Silvia Maria, Gramegna (Design International, 2022)
Associate Professor in Interior and Spatial Design at Politecnico di Milano. She has been visiting professor at Tsinghua University, Beijing (China); Kookmin University, Seoul (South Korea); Hosei University, Tokyo (Japan) and many others. She designed professional projects in China, Japan, USA, Europe, UK and UAE, as founder of Senselab, most of them awarded and selected by international juries. Some of her researches and products have been selected by ADI-Index 2019, Italian Design Ambassador 2020, 2021; awarded Eccellenze della Lombardia. She exhibited her works at Biennale di Venezia 2010, 2011, 2021; Triennale di Milano 2018. The relationships between senses, time, spaces and design are developed in education, conferences, publications and professional works. She is the author of Storie di Architettura attraverso i sensi (Stories of architecture through the senses, Bruno Mondadori, 2000), Invisible Architectures. Experiencing places throught the senses of smell (Skira, 2006), Sensi, tempo e architettura (Senses, time and architecture, Postmedia Books, 2012), Sensefulness, new paradigms for Spatial Design (Postmedia Books, 2019), and the book Extended Store. How digitalization effects the retail space design, written in collaboration with the author Yuemei Ma (FrancoAngeli, 2021), as well as many other international publications.